2013
DOI: 10.5812/hepatmon.8988
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein Profiles and Response to Pegylated Interferon Plus Ribavirin Combination Therapy in Patients With Chronic HCV Genotype 1b Infection

Abstract: BackgroundAbnormal serum lipid profiles have been noted in patients with chronic hepatitis C virus (HCV) infection. Moreover, many reports suggest that serum lipoprotein profiles are more profoundly distorted in patients with HCV G1b infection who have an unfavorable response to pegylated interferon (peg-IFN) plus ribavirin (RBV) combination therapy. However, after the discovery of single nucleotide polymorphisms near the IL28B gene (rs8099917 and rs12979860) as potent predictive factors affecting the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…(31)(32)(33) On the other hand, several studies found that HCV genotype was the only significant predictor for treatment response. (34)(35)(36)(37) The study conducted by Yu et al (2008) in Taiwan showed that HCV genotype and rapid virologic response (RVR) were the strongest independent factors associated with a virologic response, followed by treatment duration and low baseline viral load. (21) Quality of life is a significant factor when making decisions about HC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(31)(32)(33) On the other hand, several studies found that HCV genotype was the only significant predictor for treatment response. (34)(35)(36)(37) The study conducted by Yu et al (2008) in Taiwan showed that HCV genotype and rapid virologic response (RVR) were the strongest independent factors associated with a virologic response, followed by treatment duration and low baseline viral load. (21) Quality of life is a significant factor when making decisions about HC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of lipid metabolism in HCV infection has been investigated, and it is clear that HCV infection predisposes an individual not only to dyslipidemia, but also to hepatic steatosis [ 1 ] and advanced fibrosis. Moreover, dysregulated lipid metabolism in chronic HCV infection may predict the efficacy of interferon (IFN)-based antiviral therapy [ 2 , 3 ]. Although many studies have reported abnormal serum lipid levels in HCV infection, especially low levels of total cholesterol (TC) [ 4 ] and low-density lipoprotein cholesterol (LDL-C) [ 5 ], little is known about the serum triglyceride (TG) profile in HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…HCV-infected patient's diagnosis and treatment has become a clinical challenge due to association of severe autoimmune features. The HCV infection history in terms of chronic toxicity and disease progression seems to be largely determined by the host immune response to virus-infected hepatocytes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%